KONSTRUKSI TES KEBAHASAAN UAS SD DI KABUPATEN MADIUN - Samsiyah, Nur; Kartikasari H.S, Apri; Efilia, Crisna (Premiere Educandum, 2015)
Language learning is aimed to achieve proficiency properly. To achieve objectivesof language learning cannot be separated from aspects of grammar. One way toachieve the grammatical aspect is by using a test. The purpose of language test isability and skill in language not knowledge about language. Range of aspects aremeasured based on the types of tests used in the test questions at the end of thelearning/ formative. This research aimed to determine language aspects tested at theend of each semester. This study used a qualitative approach and data sources in theform of the exam end of semester 1 and 2 grade 1 to grade 6. Techniques of datacollection is done by collecting data source in the field and read the data source.Data analysis phase consists of three stages: data reduction, classification,presentation of data and drawing conclusions.The results showed there were aspectsof language such as phonology, morphology aspect which consists of free and boundmorpheme, the process of reduplication or repetition, syntactic aspects that formphrases and sentences as well as aspects such as semantic meaning.Keywords: Final Exam, Linguistic aspects